PENGARUH MODERNISASI SISTEM ADMINISTRASI DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA BATAM SELATAN - Firli, Irfani; Efriyenti, Dian (SCIENTIA JOURNAL, 2021)
There are still many taxpayers who do not understand using the e-filing system and knowledge of taxation resulting in compliance in carrying out their obligations is still not optimal. Therefore, the Directorate General of Taxation continues to modernize the system and media to gain tax knowledge. This study aims to determiine whether thee Modernization of Tax Administratiion and Knowledge Systems has an effect on Taxpayer Compliance. The population of this ressearch is WPOP registerred at KPP Pratama Batam Selatan, amounting to 346,894. The sampling technique used a random sampling technique with the slovin formula, so that the sample amounted to 100 respondents. Data analysis techniques used descriptive analysis, instrument testing, clasical asumptions, multiiple linear analysiis, and hypotheisis testiing. The results of this study indicate that the Modernization of the Tax Administration System has a significant efect on taxpayer compliance with a significant value of 0.015 < 0.05. Tax knowledge has a signifficant effect on taxpayer compliance with a signifficant value of 0.000 < 0.05. Modernization of Tax Administration and Knowledge Systems simultaneousli affects the compliance of taxpayers registered at KPP Pratama South Batam.